2015
DOI: 10.1136/tobaccocontrol-2015-052529
|View full text |Cite
|
Sign up to set email alerts
|

Hiding the tobacco power wall reduces cigarette smoking risk in adolescents: using an experimental convenience store to assess tobacco regulatory options at retail point-of-sale

Abstract: Objectives This experiment tested whether changing the location or visibility of the tobacco power wall in a life sized replica of a convenience store had any effect on adolescents’ susceptibility to future cigarette smoking. Methods The study was conducted in the RAND StoreLab (RSL), a life sized replica of a convenience store that was developed to experimentally evaluate how changing aspects of tobacco advertising displays in retail point-of-sale environments influences tobacco use risk and behavior. A ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 29 publications
(33 reference statements)
0
43
0
1
Order By: Relevance
“…A survey of 1401 British youth showed that noticing tobacco displays was associated with higher levels of future intentions to smoke (susceptibility) 11 . Also, an experimental study among US adolescents showed that hiding tobacco displays significantly reduced susceptibility compared to leaving it exposed 10 . For policy, our results provide evidence for initiating a ban on tobacco displays at POS in lowand middle-income country settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of 1401 British youth showed that noticing tobacco displays was associated with higher levels of future intentions to smoke (susceptibility) 11 . Also, an experimental study among US adolescents showed that hiding tobacco displays significantly reduced susceptibility compared to leaving it exposed 10 . For policy, our results provide evidence for initiating a ban on tobacco displays at POS in lowand middle-income country settings.…”
Section: Discussionmentioning
confidence: 99%
“…The ban on tobacco displays at POS is essential, given evidence of their relationship with tobacco exposure among youth [9][10][11][12][13][14][15] . In Asia, Thailand was the first country to implement the ban in 2005, which has been shown to have reduced exposure to tobacco marketing at POS 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Participants for this study were a subset of individuals from a larger experimental study that examined whether changing the placement or visibility of the tobacco power wall influences smoking risk in adolescents (Shadel et al, 2016). The experiment was conducted in the RAND StoreLab (RSL; see description below), a true-to-life convenience store that was developed to experimentally evaluate how changing aspects of tobacco advertising at POS influences tobacco use risk and behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Product posters, including those for tobacco, are displayed on the walls, shelves, and windows of the RSL. Additional details and photographs are provided in Shadel et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation